Primary squamous cell carcinoma of the breast: A case report and review of the literature - Wu, Yaping; Chen, Zhiying; Li, Wei; Wang, Fengguang; Zhang, Yongchun (Frontiers in Oncology, 2023)
Primary squamous cell carcinoma (PSCC) of the breast, as a rare metaplastic breast cancer, currently has limited clinical data on its biological behavior, treatment and prognosis. At present, the optimal treatment of this tumor is still controversial, and no standard treatment has been established. We reported a case of a 56-year-old woman with a mass on the right breast. She underwent a modified radical mastectomy and lymph node biopsy, which revealed that the tumor was a metaplastic squamous cell carcinoma with axillary lymph node metastasis, followed by traditional adjuvant chemotherapy and radiotherapy. The patient re-examined by PET/CT after two years in May 2017 and found a recurrence in the right chest wall, and resection of the recurring lesion was resected, then she was given postoperative adjuvant radiotherapy and chemotherapy. In August 2019, the patient re-examined by PET/CT, and there was lung and mediastinal lymph node metastasis. After 4 cycles of albumin paclitaxel plus cisplatin chemotherapy combined with nivolumab immunotherapy, the patient achieved complete response (CR), and then switched to nivolumab immune maintenance therapy. So far, no obvious metastasis has been seen. In combination with this patient and some previous clinical studies, we believe that surgical treatment is necessary for PSCC of the breast. For breast PSCC, we believe that paclitaxel and cisplatin chemotherapy regimens and adjuvant radiotherapy are effective, but it may be resistant to radiotherapy. Immunotherapy may prolong the survival of patients with PSCC of the breast, but more clinical data are still needed to confirm it.